The changing pattern of clinical Mycobacterium avium isolation in the Netherlands - van Ingen, J; Hoefsloot, W; Dekhuijzen, P N R; Boeree, M J; van Soolingen, D (The international journal of tuberculosis and lung disease, 2010)
National Mycobacteria Reference Laboratory, The Netherlands. To assess the role of factors other than laboratory improvements in the increasing frequency of isolation of non-tuberculous mycobacteria (NTM) in the Netherlands; laboratory improvements are often considered key factors in this increase. Laboratory database study. All clinically isolated NTM referred to the national reference laboratory between January 2000 and January 2007 were retrieved from the laboratory database and categorised by species, patient age group and sample origin. Data were compared with national demographic data. Clinical Mycobacterium avium isolates accounted for most of the increase in referred NTM. The number of respiratory M. avium samples in patients aged >40 years increased over time. This age group increased in size during the study. In this age group, the prevalence of chronic obstructive pulmonary disease (COPD) increased during the study period. M. avium isolation from lymph nodes in children remained stable, whereas extra-pulmonary M. avium isolation in the middle age group, including human immunodeficiency virus associated bloodstream isolates, decreased. The increasing NTM notification in the Netherlands is unlikely to have been a result of laboratory improvements alone: the ageing population with an increasing prevalence of COPD is likely as important. Environmental characteristics may specifically favour M.avium.